From Unsuccessful Attempts by Non Medical Personal to Surgery in Removing Rectal Foreign Bodies: Case Report - Yıldız, Mustafa; Mutlu, Bengü; Bozdemir, Mehmet Nuri; Gül, Evrim; Gürger, Mehtap; Alataş, Ömer Doğan; Girgin, Mustafa (Acil Tıp Uzmanları Derneği, 2013)
Intentional or unintentional insertion of foreign objects into the anus and rectum is a well-described phenomenon. A 40 year old man and 35 year old man presented to the emergency department after insertion of a high pressure container of tanning spray and insertion of a soda pop bottle into their rectum respectively. After an unsuccessful attempt to extract the foreign body at home, one patient tried to remove the foreign body by a piece of string which also stayed in the rectum. The foreign body was grasped with clamps and gently extracted in one case. In the other case, the foreign bodies were removed after sphincterotomy. To the best of our knowledge this is first case involving an attempt to remove the foreign body by a piece of string. We consider that removing a foreign body using string may involve a high risk of perforation, haemorrhage and infection. We describe two cases who presented at the emergency department with a rectal foreign body

Kasıtlı veya kasıtsız anüs ve rektum içine bir yabancı cisim iyi tanımlanmış bir fenomendir. Kırk ve 35 yaşındaki iki erkek hasta, sırasıyla kendi rektumları içerisine sırasıyla yüksek basınçlı sprey şişesi ve soda şişesi yerleşimi nedeniyle acil servise başvurdu. Bir vakamızda hasta evinde yabancı cisim olan soda şişesini çıkarmak için tel ile uğraşmasına rağmen çıkaramamış ve yabancı cisim rektumda kalmıştır. Yabancı cisim klemple yakalanıp çıkarılmıştır. Diğer vakada sfinkterotomi sonrası yabancı cisim çıkarılmıştır. Bilebildiğimiz kadarıyla vakamız tel ile yabancı cismi çıkarma çabası ile ilgili ilk vakadır. Tel ile yabancı cismin çıkarılması çabasının perforasyon, kanama ve enfeksiyon için yüksek risk taşıdığını düşünüyoruz. Rektal yabancı cisim nedeniyle acil servise başvuran iki olguyu sunduk.
Hastanın Kendi Kendine Çıkarma Girişimi Başarısız Olması Nedeniyle Cerrahiye Giden Rektal Yabancı Cisim: Olgu Sunumu